Factors Affecting Customer Satisfaction: An Empirical Study on Telecommunication Sector in Bangladesh. - Md. Habibur Rahman, Md. Mahmudul Huq & Mohammad Enayet Ullah (Academic Journal on Science, Technology, Engineering & Mathematics Education, 2023)
Factors affecting customer satisfaction is of worth importance in order to know the reasons or the factors which are responsible to create satisfaction among customers for a particular brand. Customer satisfaction is established when brand fulfills the needs and desires of customers. In this research study, the subscribers of telecom sector of the mobile service providers like Grameenphone (GP), Banglalink, Robi, and Airtel operating in Bangladesh were targeted as the population while Price Fairness and Customer Services were taken as predicting variables towards Customer Satisfaction as criterion variable. The results showed that both the factors significantly contributed to explain customer satisfaction but comparatively price fairness had the larger impact on customer satisfaction than customer services.